Safety Net Provider Attitudes Toward Smoking Cessation Treatment - Meredith, Lindsay R.; Baskerville, Wave-Ananda; Friedman, Theodore C.; Hurley, Brian; Dixon, Tasha; Mtume, Norma; Rodriguez, Luz; Lopez, Briana; Hsieh, Susan; Ray, Lara A. (Frontiers in Psychiatry, 2021)
Background: Cigarette smoking, which poses significant health risks, is prevalent among vulnerable populations commonly treated by safety net providers. A large-scale implementation science project on specialty tobacco use treatment was launched within the Los Angeles County Health Agency. The first phase of this study seeks to summarize and compare smoking cessation treatment attitudes of providers at the Department of Health Services (DHS) and Department of Mental Health (DMH). Methods: In total, 467 safety net health care providers (DHS = 322; DMH = 145) completed a survey inquiring about attitudes on smoking cessation treatment consisting of locally developed items and those informed by a scale on readiness for organizational change. Descriptive statistics and non-parametric tests were conducted to examine treatment attitudes for DHS and DMH providers. Results: Between agencies, providers largely reported similar attitudes on smoking cessation treatment and expressed positive beliefs regarding the efficacy of smoking cessation aids. Providers slightly or moderately agreed with being prepared to identify and diagnose tobacco use among patients. DMH providers stated that identification of tobacco use was less in line with their job responsibilities (p <.0001) and less strongly agreed that varenicline is effective for smoking cessation (p =.003), compared with DHS providers. Conclusions: Providers supported smoking cessation aid efficacy but may benefit from additional training on identification and treatment of tobacco use. These findings support the implementation of specialty tobacco cessation treatment programs with training on medications in safety net health care systems, which has the potential to yield large-scale public health benefits.